2019
DOI: 10.1161/circimaging.118.007865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Initial Shunt Type on Echocardiographic Indices in Children After Single Right Ventricle Palliations

Abstract: Background Heart size and function in children with single right ventricle (RV) anomalies may be influenced by shunt type at the Norwood procedure. We sought to identify shunt-related differences during early childhood after staged surgical palliations using echocardiography. Methods We compared echocardiographic indices of RV, neoaortic, and tricuspid valve size and function at 14 months, pre-Fontan, and 6 years in 241 subjects randomized to a Norwood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Retrospective studies of patients with functional SV with long-term follow-up data reported other risk factors that negatively impact prognosis including arrhythmia, atrioventricular valve regurgitation, and prolonged pleural effusion drainage [ 6 , 34 ]. Two large consortium studies (Single Ventricle Reconstruction Trial from North America [ 4 , 5 , 35 ] and the Australian and New Zealand Stage III Registry [ 8 ]) followed patients with functional SV physiology over time. In these studies, atrioventricular valve regurgitation and heterotaxy were predictors of mortality [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies of patients with functional SV with long-term follow-up data reported other risk factors that negatively impact prognosis including arrhythmia, atrioventricular valve regurgitation, and prolonged pleural effusion drainage [ 6 , 34 ]. Two large consortium studies (Single Ventricle Reconstruction Trial from North America [ 4 , 5 , 35 ] and the Australian and New Zealand Stage III Registry [ 8 ]) followed patients with functional SV physiology over time. In these studies, atrioventricular valve regurgitation and heterotaxy were predictors of mortality [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, atrioventricular valve regurgitation and heterotaxy were predictors of mortality [ 8 ]. But source of pulmonary blood flow (modified Blalock-Taussig shunt versus RV to the pulmonary artery conduit (Sano shunt)) at stage I did not change long-term prognosis [ 4 , 5 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the findings of Sobh et al, 16 who found that RVEF by CMR was 54% among 6- to 11-year-old children with HLHS and Fontan circulation, and with previous findings from the SVR cohort showing no difference in RVEF between shunt groups as measured by echocardiography at 6 years of age. 17 Whereas systolic function is relatively preserved, further evaluation of the CMR and echocardiography data will be important to understand the effect of age and of shunt type on diastolic function and other indicators of cardiac dysfunction. The preteen period may be too early to detect systolic dysfunction by CMR.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular function was measured with CMR as well as with 2-dimensional transthoracic echocardiography. Participants who underwent CMR were 10.9 years of age (interquartile range, 10.4-11.5) at the time of CMR, and, compared with those who did not have CMR, they had a significantly shorter hospital length of stay after the Norwood procedure (22 [interquartile range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] versus 28 days [interquartile range, 20-39]; P=0.02) and were more likely to be male (66% versus 47%; P=0.01; Table S2). Among the 177 participants who underwent CMR, RVEF was measurable in 168 (95%); the mean±SD for the overall cohort was 51.5±8.6% (RVPAS 51±9.…”
Section: Right Ventricular Functionmentioning
confidence: 99%
“…108 Serial monitoring of RV function with the use of echocardiography measures such as fractional area change, RV strain, and tricuspid annular plane systolic excursion can help in early detection and risk stratification. 107,[109][110][111][112][113] Although the initial selection of surgical strategy does not seem to have important impact on RV systolic function, 105,[114][115][116][117][118][119] strategies for medical preservation of the RV may be a promising avenue of future study. Recent data suggest that digoxin use in the interstage is associated with better survival, likely related to an effect of RV remodelling, 120 but other potential medical therapies deserve similar exploration.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%